From main-stream to full-service schools : an exploration of teachers' attitudes towards the inclusion of learners living with physical disabilities in South African schools - Molapo, Sepetla (University of Pretoria, 2018)
The Education White paper 6 gazetted that no disabled child should be left behind. It called for full-service schools but there are debates about the extent of the inclusion of disabled learners in mainstream schools. This research study explores teacher’s perceptions of the inclusion of learners living with physical disabilities in South Africa’s institutions of basic education. Ten teachers were interviewed to understand their views on how far schools have assumed the responsibilities of full-service schools. The key findings indicate that teachers who took part in the study were divided in their views on whether mainstream schools have started assuming the responsibilities of full-service schools. Some of the teachers pointed out that mainstream schools have not yet assumed the responsibilities of full-service schools and the reasons for this include; schools lacking the appropriate infrastructure to accommodate learners living with physical disabilities, teachers believe that they lack the appropriate skill set and they hold the view that learners living with physical disabilities will experience negative attitudes from their peers and teachers in mainstream schools. The salient finding indicates that some of the teachers hold negative views about the prospect of schools admitting learners living with physical disabilities. As well as certain misconceptions and prejudices about learners living with physical disabilities.